2020
DOI: 10.1186/s12935-020-01614-z
|View full text |Cite
|
Sign up to set email alerts
|

Combination strategies to overcome resistance to the BCL2 inhibitor venetoclax in hematologic malignancies

Abstract: Venetoclax has been approved by the United States Food and Drug Administration since 2016 as a monotherapy for treating patients with relapsed/refractory chronic lymphocytic leukemia having 17p deletion. It has led to a breakthrough in the treatment of hematologic malignancies in recent years. However, unfortunately, resistance to venetoclax is inevitable. Multiple studies confirmed that the upregulation of the anti-apoptotic proteins of the B-cell lymphoma 2 (BCL2) family mediated by various mechanisms, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 113 publications
1
36
0
Order By: Relevance
“…Apoptosis is a form of programmed cell death that maintains homeostasis in the body ( Yue et al, 2020 ). Unsurprisingly, malignant cells often acquire the ability to evade apoptosis.…”
Section: Regulation Of Tumorigenesis and Progressionmentioning
confidence: 99%
“…Apoptosis is a form of programmed cell death that maintains homeostasis in the body ( Yue et al, 2020 ). Unsurprisingly, malignant cells often acquire the ability to evade apoptosis.…”
Section: Regulation Of Tumorigenesis and Progressionmentioning
confidence: 99%
“…Similarly, mutations in BCL2, detectable months earlier than clinical progression using droplet digital PCR, have been shown to decrease the efficacy of venetoclax [90]. Activated T-cells produce IL-4 and IL-21 that can stimulate the CD40-CD40L interaction and increase the expression of the anti-apoptotic factor BCL-xL, among other factors [91].…”
Section: Role Of the Immune System In Resistance To Treatmentmentioning
confidence: 99%
“…Combination of ibrutinib and venetoclax would reduce the probabilities of proliferation of clones with resistant mutations in both pathways simultaneously. Additionally, it has been shown that microenvironment cytokines (IL-10, sCD40L or CpG-ODNs) can significantly reduce the synergy of the combination in an NF-κB-dependent manner [91,92].…”
Section: Role Of the Immune System In Resistance To Treatmentmentioning
confidence: 99%
“…BCL2 family proteins control the intrinsic apoptotic pathway, and venetoclax is a novel, oral BH3-mimetic and highly selective BCL2 inhibitor that is very effective in overcoming the anti-apoptotic effect of BCL2. Venetoclax has been approved in CLL both in the relapsed [26] and frontline setting [27] , and it is also being studied in the frontline setting for double expressor DLBCL [28] and the relapsed setting for mantle cell lymphoma (MCL) [29] . There are a variety of mechanisms for resistance to venetoclax.…”
Section: Resistance To Targeted Therapiesmentioning
confidence: 99%